(3OjhGf CHj JeGes - (3CHh JeGe GdWGFj , CHh JeGe MHjH Hf ChS Hf GdMGQK GdWGFj,J (B231 (3g` s
(3ChdgG (B:s
(3bGd GHhJeGe jeOM eMeO Hf jhSa(B: (3YSi hWf jOfhG Hge hdYdeG hEf JYbH GdCjGe ajge aQHeG s
(3BNQgG (B:s
(3aj eOM GdhGKb HGddg(B: (3heJi jMjW HhUa eLOc hGUa dh cGf Mhd dSGfg GdeLghOG s
(3GdfSNI HgG MhGTs
(3Ydi ghGeTgG JbjjGJ cKjQIs
(3fSNI NGeSIs
(3efbhdI Yf fSNI bhHdJ HNW CHj MaU Hf HQO GdcGJH hfSNI GHf HQO bQCgG GHfg CHhGdMSf Ydj GdhRjQ CHj GdbGSe EHQGgje Hf eMeO GdEbdjdj HQhGjI GdUhdj s
(3hQO CjVkG JMJ Qbe (B475(3, (B667(3, (B873(3, (B917(3, (B2202(3, (B3247 s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs